Multi-disciplinary Teamwork of Community Care Staff in Service Provisions for the Elderly - FUJITA, Masaaki; HAMAMURA, Akinori; KOIZUMI, Koki; MATSUSAKA, Nobuou; HIGASHI, Toshio; IMANAKA, Etsuko (Rihabiritēshon igaku, 1998)
Community care professionals were asked to complete a questionnaire concerning individual disabled elderly people living at home for whom they were currently providing care services in 6 municipalities, where multi-disciplinary meeting had been held regularly. Six hundred and fifteen subjects were reported in this study. The multidisciplinary meetings brought better results in identification of the insufficient information on the subjects, assessment of their health and social care needs, and coordination of care services needed for them compared to the performance by one professional or meetings within one discipline. Although the period of coordination of the services was significantly longer in the multi-disciplinary meetings than in the other procedures, there was no significant difference in the period of assessment of the subject's needs between the types of the procedures. Therefore, it is suggested that the multi-disciplinary meetings play an important role in order to achieve an appropriate care management process. However, the role of coordinator of services become important to shorten the period of the coordination. In all the municipalities, public health nurses contributed to coordination of services. In the municipalities where cooperation between agencies was good, social workers and PTs or OTs as well as public health nurses mainly acted as the coordinator. By contrast, where few disciplines other than public health nurses coordinated services, there were some problems in cooperation between agencies. It is likely that there were some limitations of coordination of services only by public health nurses. That is to say, it is suggested that one or two disciplines like social workers and PTs or OTs besides public health nurses should take part of the coordinator depending on the clients' needs.